Mites of the genus Dolicheremaeus Jacot from the Philippines (Acari Oribatida: Otocepheidae) - Corpuz-Raros, Leonila A. (2000)
Thirty-six species of Dolicheremaeus are reported from the Philippines of which 30 are new to science and one is a new record. A key to Philippine mites is given, and all species are described and illustrated. The new name, D. hammerae is proposed as replacement for D. lineolatus Hammer 1981 from Java, which was found to be a junior homonym of D. lineolatus Balogh and Mahunka 1967 from Vietnam.
Keywords: Mites; Soil mites